Перегінський різьбярно-меблевий осередок - Дяків, М. (Інститут народознавства НАН України, 2008)
In the article is described the premise of renascence of burnishing in the Pereginsk, in culcation of artistic style into craft, instillation of individual approach to the creation of manufactured article, professional design tuning up historic trend. All these factors have become obligatory standard and demand of professional approach that have defined the furter development of professional furnishing and promoted the development of artistic.